Urban-Rural Disparity in Helicobacter Pylori Infection–Related Upper Gastrointestinal Cancer in China and the Decreasing Trend in Parallel with Socioeconomic Development and Urbanization in an Endemic Area - Xiaoduo Wen (Ubiquity Press, 2017)
Background: Globally China has the largest urban-rural disparity in socioeconomic development, and the urban-rural difference in upper gastrointestinal cancer (UGIC) is similar to the difference between developed and developing countries. Objectives: To describe urban-rural disparity in UGIC and to emphasize prevention by socioeconomic development and urbanization in China. Methods: Age-standardized incidence rates (ASRs) of cancers in 2012 were compared between urban Shijiazhuang city and rural Shexian County, and trends from 2000-2015 in Shexian County were analyzed. Findings: Compared with urban Shijiazhuang city, the ASR of gastroesophageal cancers in rural Shexian County was 5.3 times higher in men (234.1 vs 44.2/100,000, 'P' '<' '.'01) and 9.1 times higher in women (107.7 vs 11.8/100,000, 'P' '<' '.'01). This rural-urban disparity in UGIC is associated with differences in socioeconomic development in annual gross domestic product (GDP) per capita of US$2700 vs US$6965, in urbanization rate of 48% vs 100%, and in adult 'Helicobacter pylori' infection prevalence of 75% vs 50%. From 2000-2015, the GDP per capita in Shexian County increased from US$860 to US$3000, urbanization rate increased from 22.4% to 54.8%, and prevalence of 'H pylori' infection among 3- to 10-year-old children decreased from 60% to 46.1% ('P' '<' '.'01). Meanwhile, the biennial ASR of esophagogastric cancer decreased 42% in men, from 313.5 to 182.1 per 100,000 ('P' '<' '.'01), and 57% in women, from 188.6 to 80.4 per 100,000 ('P' '=' '.'00). However, lung, colorectal, and gallbladder cancers and leukemia in both sexes and breast, ovary, thyroid, and kidney cancer in women increased significantly. Despite this offset, ASR of all cancers combined decreased 25% in men (from 378.2 to 283.0/100,000, 'P' '=' '.'00) and 19% in women (from 238.5 to 193.6/100,000, 'P' '=' '.'00). Conclusions Urban-rural disparity in UGIC is related to inequity in socioeconomic development. Economic growth and urbanization is effective for prevention in endemic regions in China and should be a policy priority.